Hospital-mediated realization of enhanced recovery after surgery - Xu, Jia-jing; Tang, Xiao-ting; Mao, Mao; Yang, Qi-ning; Jiang, Lian-ping; Fu, Wei-cong; Zhou, Yong-wei; Ye, Xiang-Hong (Frontiers in Surgery, 2025)
PurposeEnhanced recovery after surgery (ERAS) has significantly benefited patients and healthcare systems; however, improvements are required, particularly in patient optimization and system implementation. Hospitals, as the main sites for medical activities, can coordinate cooperation among different departments and strategically organize various components of ERAS.MethodsIn March 2023, Jinhua Municipal Central Hospital initiated a comprehensive ERAS program, focusing on fluid and food restriction as the first task assigned. The aim was to reduce the preoperative fasting time throughout the hospital and enhance patients’ preoperative experience. We selected data from the hospital for the first quarter of 2023 as the control group and data from the second and third quarters after the ERAS program implementation as the experimental groups. The collected data included preoperative liquid fasting time (PLFt), preoperative solid fasting time (PSFt), preoperative feeling of hunger (PFoH), and preoperative feeling of thirst (PFoT).ResultsOur study included 24,829 cases. Eight departments included in the statistics revealed a significant reduction in preoperative fasting time, while the reduction of PLFt was more significant. The preoperative feeling of patients was significantly improved, which suggested that the incidence of PFoH and PFoT decreased.ConclusionsIn conclusion, implementing hospital-mediated ERAS is a feasible approach to effectively mobilize resources across departments, coordinate efforts, and address challenges in ERAS implementation. However, the long-term benefits of hospital-mediated ERAS initiatives require comprehensive ERAS protocols and longer follow-up studies for clarity. Additionally, the ERAS procedures need further improvements.